THE TEST OF PERSONALITY AND TIME: THE SPIRITUAL AND PSYCHOLOGICAL IMAGE OF THE HERO IN TWENTIETH-CENTURY ENGLISH AND UZBEK PROSE (BASED ON THE WORKS OF ERNEST HEMINGWAY AND ODIL YOQUBOV) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the spiritual and psychological portrait of the literary hero in twentieth-century English and Uzbek prose through the works of Ernest Hemingway and Odil Yoqubov. The research focuses on how historical upheavals, cultural mentality, social environment, and moral challenges shape character formation and inner emotional life. Using comparative literary analysis, psychological criticism, and contextual interpretation, the study reveals similarities and differences between Western and Eastern models of the literary hero. Hemingway’s protagonists are characterized by existential loneliness, stoic endurance, and inner discipline, whereas Yoqubov’s heroes embody moral responsibility, spiritual nobility, and strong ethical consciousness rooted in Eastern cultural values. The article concludes that both authors, despite belonging to different traditions, highlight human dignity, resilience, and the supremacy of moral and spiritual strength.